1997
DOI: 10.1074/jbc.272.19.12350
|View full text |Cite
|
Sign up to set email alerts
|

The Kinase Domain of Jak2 Mediates Induction of Bcl-2 and Delays Cell Death in Hematopoietic Cells

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-3, and IL-5 stimulate DNA synthesis and proliferation and inhibit apoptosis in hematopoietic cells. Multiple signal pathways are activated by binding of these ligands to their receptors, which share a common ␤ subunit. Janus protein kinase 2 (Jak2) binds to the membrane proximal domain of the ␤ chain and is phosphorylated on receptor ligation. To explore the role of Jak2 in the regulation of specific signal transduction pathways, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 45 publications
4
64
2
Order By: Relevance
“…Factor depletion-induced apoptosis occurred even in the presence of coumermycin implied that GyrB-Jak2 activation is insufficient to prevent apoptosis. In an apparent contradiction with our present finding, a previous report (Sakai and Kraft, 1997) demonstrated that activation of CD16 -Jak2-kinase domain fusion is sufficient to prevent cells from apoptosis and showed constitutive phosphorylation of Shc, which also has been implicated in transducing signals to the Ras-MAP kinase pathway. Our series of analysis of antiapoptosis activity of hGM-CSF using various ␤c mutants revealed that Jak2 activation through the box 1 region is essential, and that activation of either a tyrosine kinase inhibitor genisteinsensitive pathway or the MAP kinase cascade is sufficient to sustain cell viability (Liu, Itoh, and Watanabe unpublished data).…”
Section: Discussioncontrasting
confidence: 56%
“…Factor depletion-induced apoptosis occurred even in the presence of coumermycin implied that GyrB-Jak2 activation is insufficient to prevent apoptosis. In an apparent contradiction with our present finding, a previous report (Sakai and Kraft, 1997) demonstrated that activation of CD16 -Jak2-kinase domain fusion is sufficient to prevent cells from apoptosis and showed constitutive phosphorylation of Shc, which also has been implicated in transducing signals to the Ras-MAP kinase pathway. Our series of analysis of antiapoptosis activity of hGM-CSF using various ␤c mutants revealed that Jak2 activation through the box 1 region is essential, and that activation of either a tyrosine kinase inhibitor genisteinsensitive pathway or the MAP kinase cascade is sufficient to sustain cell viability (Liu, Itoh, and Watanabe unpublished data).…”
Section: Discussioncontrasting
confidence: 56%
“…Anti-apoptotic signals transduced via JAK2 have also been reported. For example, in hematopoietic cells, the kinase domain of JAK2 mediates the induction of Bcl-2 and inhibits cell death (19), and treatment with the JAK2 inhibitor AG-490 reduces the phosphorylation of PI-3-K (20) and STAT3 resulting in an increase in caspase-3 activity and Bax protein in acute myocardial infarction (21). In addition, activation of neuronal erythropoietin receptors prevents apoptosis by triggering cross-talk between the signaling pathways of JAK2 and the nuclear factor-B (22).…”
Section: Discussionmentioning
confidence: 99%
“…Jak2 activation by these cytokines seems to be involved in the induction of Bcl2 [137]. Interestingly, overboth the Ras-ERK and the PI3K-PKB pathways can have roles in cellular survival, depending on the cell type studied, ability of specific inhibitors of the MAPK and PI3K pathways will undoubtedly be of great help in determining the a number of questions remain unanswered.…”
Section: Il-3/il-5/gm-csf Receptor Signallingmentioning
confidence: 99%